Socio-Demographic Characteristics of Blood Donor in a Tertiary Care Specialized Hospital - Quader, Mohd Abul (Bangladesh Journal of Medicine, 2021)
Background: Blood donors are the backbone of a transfusion service. To ensure a safe and appropriate transfusion service, donor demography is to be optimized for proper strategic management. The purpose of this study was to assess the socio-demographic profile of blood donors to make targets for national interventions and to promote blood donation. Methods: This descriptive type cross sectional study was conducted in Transfusion Medicine department of Popular Medical College Hospital from 1st January 2015 to 30th June 2018. All the blood donors who came to donate blood in this department were included in this study. Their signed consent was obtained to include in this study with their socio-demographic determinants. Frequency, percentage and p value<0.05 were calculated for statistics. Results: Out of the 15702 blood donors, male donors were more with a ratio of 6.78:1. Though the younger age group (25-31 years) showed highest donor population (32.61%), but the younger age group (18-38 years) have maximum donation (86.21%). Unmarried donors were 59.07% among the donors and middle class income group also showed highest donors (59.09%). Student donors (30.55%) were more among the donors. Muslims donors (79.01%) were more than others religious donors. Regarding education level of donors, higher secondary and above level showed highest donation (90.97%) which was statistically significant (p<0.001). Among the donors 78.05% showed their future intension to donate. Conclusions: Works on differences in socio-demographic characteristics of blood donors in times of increasing demand appears to be fruitful to target national interventions and to promote blood donation. Bangladesh J Medicine July 2021; 32(2) : 113-119